Respuesta :

oreo85

Answer:

x - y = 2

Step-by-step explanation:

First of all, you would combine like terms, giving you 4x - 4y + 1 = 9.

Next, subtract the numbers, which gives you 4x - 4y = 8.

Finally, divide both sides by 4, which will come to the conclusion of x - y = 2, the simplest form of which this equation can be broken down to.

Answer:

[tex]x = y + 2[/tex]

Step-by-step explanation:

given

[tex]4x + 1 = 9 + 4y[/tex]

[tex]4x = 4y + 9 - 1[/tex]

[tex]4x = 4y + 8[/tex]

making x the subject by dividing through by 4

[tex] \frac{4x}{4} = \frac{4y + 8}{4} [/tex]

[tex]x = \frac{4y + 8}{4} [/tex]

[tex]x = \frac{4y}{4} + \frac{8}{4} [/tex]

[tex]x = y + 2[/tex]